The Relationship Between Parental and Teachers’ Autonomy Support, Enjoyment, Self-Efficacy, Academic Effort and P·E class Flow by Middles School Students Participating in P·E Classes - Hunhyuk Choi; Seongkwan Cho (Cheyuk gwahag yeon-gu, 2021)
Purpose The aim of this study was to examine how middles school students in physical education class perceived relations between parental and teacher’s autonomy support, enjoyment, self-efficacy, academic effort, and P · E class flow. This study also investigate the mediating effects of enjoyment, self-efficacy, and academic effort on the relations between parental autonomy support and P · E class flow and between teacher’s autonomy support and P · E class flow. Methods For this study, 323 middle school students completed surveys to measure their perceptions of parental and teacher’s autonomy support, enjoyment, self-efficacy, academic effort, and P · E class flow. SPSS 24.0 was used to calculate descriptive statistics, reliability, and correlations. Amos 22.0 was utilized for confirmatory factor analysis, convergent validity, discriminant validity, and structural equation modeling. Additionally, 2000 bootstrap samples were requested for the mediation effect analysis. Results First, parental autonomy support was positively predictive of enjoyment and self-efficacy. Second, teacher’s autonomy support positively influenced enjoyment and self-efficacy. Third, enjoyment and self-efficacy positively affected academic effort. Forth, academic effort was positively related to P · E class flow. Fifth, there were partial mediating effects of enjoyment, self-efficacy, and academic effort on the relationship between parental autonomy support and P · E class flow. Lastly, there were partial mediating effects of enjoyment, self-efficacy, and academic effort on the relationship between teacher’s autonomy support and P · E class flow. Conclusions The study found that teachers' autonomy support was stronger predictive of student’s P · E class flow in physical education class than parent's autonomy support was. The finding is meaningful in that it is worth providing and utilizing practical knowledge from an educational perspective.